Dual-function forests in the returning farmland to forest program and the flexibility of environmental policy in China. Issue 78 (January 2017) - Zinda, John Aloysius; Trac, Christine J.; Zhai, Deli; Harrell, Stevan
Highlights: The RFFP compensates farmers for planting trees on retired farmland. Much "ecological forest" planted is "dual-function forest" composed of tree crops. Varying local outcomes show commercial varieties do not ensure tree establishment. Residents and officials acting strategically reshaped the RFFP in unpredictable ways. Dual-function forests recast the social and environmental significance of the RFFP. Abstract: The Returning Farmland to Forest Program (RFFP; tuigeng huanlin gongcheng ), which compensates farmers for cultivating forest on previously non-forested land, is central among the "ecological construction" programs that have transformed landscapes across China. Under the RFFP, state authorities have redefined large areas of land as afforestation area intended to provide environmental services including erosion control, carbon sequestration, and biodiversity regeneration. Tensions among the program's social and environmental objectives as well as the combination of formal rigidity and practical flexibility manifest in ambiguous forest classifications and tremendous variation in outcomes. The RFFP centers on two forest categorizations: ecological forest, intended to rehabilitate environmental services, and commercial forest, which may provide lesser ecological benefits but delivers more immediate economic benefits to households. RFFP policy documents designate "dual-function species" that can be planted as "forests with a primary goal of ecological service provision which also generate commercial value." A substantial portion of "ecological forests" are dual landscapes intended to accomplish both environmental and socioeconomic goals. Drawing from cases in Yunnan, Sichuan, and Hainan provinces, this paper examines the processes of central policy-making and local implementation through which dual-function forests have proliferated, showing how rural residents have responded to the risks and promises of dual-function forests and exploring implications for rural livelihoods and landscapes. While they might be expected to bring win-win outcomes, the performance of dual-function forests on social and environmental goals depends on how local officials and residents respond to the program. Their proliferation demonstrates tensions inherent in state projects aimed at generating both environmental and economic values from rural landscapes.